Territórios nômades: uma avaliação da política de apropriação do espaço público pelos ambulantes da Feira da Parangaba em Fortaleza - Gadelha, Paulo Elson Fernandes (2022)
This work aims to evaluate the repercussions of the public policy of use of public space by the street vendors of the Parangaba fair in Fortaleza, glimpsing the action of the State in the discipline and urban supervision. As is well known, public space reflects the tensions of the process of production and reproduction of urban space and the existing public-private interest conflicts. In other words, the different ways in which public space is appropriated result from the way society is organized, which involves the distribution of income among individuals and their production and consumption needs. In Brazil, the number of urban informal workers has increased dramatically, following the latest economic crises. Recent history shows that the economic conflicts associated with the expansion of informality only demonstrate the permanence, and even the worsening, of socioeconomic inequalities. Specifically, the research describes the transformation and application of urban policy instruments in relation to street commerce in the city of Fortaleza, as well as reveals the ability of street commerce to resist disciplinary and coercive public actions. A research methodology is adopted, centered on a case study that is structured from the evaluation of the impacts of the activity of street commerce in the surroundings of Lagoa da Parangaba, located in the city of Fortaleza, state of Ceará. For years, two fairs – the free fair and the car fair – dominated the space around the Lagoa, causing inconvenience and harm to the environment, pedestrians and the neighborhood itself. The results of the evaluation show that, despite the negative repercussion of health and safety problems, and of disrespect for current norms, it is not possible to neglect that the informalization of street vendors is associated with technological and conjunctural unemployment, as well as with social exclusion and precariousness of work.